G-CSF influences mouse skeletal muscle development and regeneration by stimulating myoblast proliferation - Hara, Mie (The Rockefeller University Press, 2011)
After skeletal muscle injury, neutrophils, monocytes, and macrophages infiltrate the damaged area; this is followed by rapid proliferation of myoblasts derived from muscle stem cells (also called satellite cells). Although it is known that inflammation triggers skeletal muscle regeneration, the underlying molecular mechanisms remain incompletely understood. In this study, we show that granulocyte colony-stimulating factor (G-CSF) receptor (G-CSFR) is expressed in developing somites. G-CSFR and G-CSF were expressed in myoblasts of mouse embryos during the midgestational stage but not in mature myocytes. Furthermore, G-CSFR was specifically but transiently expressed in regenerating myocytes present in injured adult mouse skeletal muscle. Neutralization of endogenous G-CSF with a blocking antibody impaired the regeneration process, whereas exogenous G-CSF supported muscle regeneration by promoting the proliferation of regenerating myoblasts. Furthermore, muscle regeneration was markedly impaired in G-CSFR–knockout mice. These findings indicate that G-CSF is crucial for skeletal myocyte development and regeneration and demonstrate the importance of inflammation-mediated induction of muscle regeneration.